The Right to Oblivion in a Comparative European Perspective (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This paper analyses the “Right to be ‘medically’ forgotten”  – starting with a brief introduction on how this concept has evolved during the last decades – with specific regard to the medical field. It focuses on cancer survivors and their right to live a life without injustices and discriminations caused by the stigma of the disease. By using the comparative method, this work aims to address the European perspective on the issue, as well as the need for a more harmonised legal framework.
Keywords: oblivion; cancer survivors; legal medicine; comparative law; European law